Lupenone improves motor dysfunction in spinal cord injury mice through inhibiting the inflammasome activation and pyroptosis in microglia via the nuclear factor kappa B pathway - Fudong Li; Xiaofei Sun; Kaiqiang Sun; Fanqi Kong; Xin Jiang; Qingjie Kong (Neural Regeneration Research, 2024)
Spinal cord injury-induced motor dysfunction is associated with neuroinflammation. Studies have shown that the triterpenoid lupenone, a natural product found in various plants, has a remarkable anti-inflammatory effect in the context of chronic inflammation. However, the effects of lupenone on acute inflammation induced by spinal cord injury remain unknown. In this study, we established an impact-induced mouse model of spinal cord injury, and then treated the injured mice with lupenone (8 mg/kg, twice a day) by intraperitoneal injection. We also treated BV2 cells with lipopolysaccharide and adenosine 5′-triphosphate to simulate the inflammatory response after spinal cord injury. Our results showed that lupenone reduced IκBα activation and p65 nuclear translocation, inhibited NLRP3 inflammasome function by modulating nuclear factor kappa B, and enhanced the conversion of proinflammatory M1 microglial cells into anti-inflammatory M2 microglial cells. Furthermore, lupenone decreased NLRP3 inflammasome activation, NLRP3-induced microglial cell polarization, and microglia pyroptosis by inhibiting the nuclear factor kappa B pathway. These findings suggest that lupenone protects against spinal cord injury by inhibiting inflammasomes.